THORACIC EPIDURAL AS THE SOLE ANESTHETIC TECHNIQUE FOR COLORECTAL SURGERY IN AWAKE PATIENTS WITH SEVERE RESPIRATORY DYSFUNCTION - Cvetanović, Milica (Acta medicae Medianae, 2026)
The report presents a case of major abdominal surgery performed in an awake patient with a high surgical risk due to severe chronic obstructive pulmonary disease. Elective sigmoid colon resection was successfully performed under thoracic epidural anesthesia as the sole anesthetic technique. The patient remained awake and moderately sedated throughout the procedure, which was well tolerated. The applied anesthetic approach itself, which has been proven to reduce the intraoperative and postoperative risks of cardiac, respiratory, and gastrointestinal complications, significantly contributed to a faster postoperative recovery with minimal complications. In a situation where the risk of general endotracheal anesthesia outweighs its benefits, thoracic epidural anesthesia was opted for as the sole anesthetic technique. This approach avoided potentially severe complications, while the additional advantages of epidural anesthesia and analgesia accelerated recovery, especially in a high-risk patient.